História da educação matemática no estado de Mato Grosso : o movimento da matemática moderna no município de Juara no período de 1970 a 1990, a partir da Escola Estadual Oscar Soares - Santos, Reginaldo José dos (2013)
The present dissertation bring how deep cloth to apprend the singularities of the colonization process of the city Juara, largest four cities which compose the Vale do Arinos micron-region, in the north part of the Mato Grosso State, in the period of 1970 a 1980 (Pre-colonization) and 1981 a 1990 (Post colonization). This intense first considered in the process of colonization. In this context, the proposal is to investigate the presents pedagogic practices in Mathematic teach developed at the Oscar Soares States School, in the period study. This investigation situate himself in the field of the Education Mathematic History in Brazil. The analysis were bound starting of various wrinteen fountains: proves, classroom diaries, final result’s record, inspection’s book term, documents of the and about the school how regulations and decree, curriculum matrixs teach programs, didactics books which permeated the Mathematic teach pratices. There the writeen fountains were considered how fountains photography and interviews. The subjects selecteds for the testimonies were teachers which ministered math class, directors, employees and former student, totalizing eighteen interviewee, which of some manner, were presents in the historical constitution of the education, as well as in the trajectory of the Mathematic teaching in this school. Writeen documents were found in personais archive of interviewee, school in study public library and pedagogical support. The photography were localized starting of the narration of the witness accounts and at the Savoine Cultural Center in Juara. Guided himself as to the theorical referential, in the conception history of Jacques le Goff in the study, it was possible to perceive in the pedagogical practices of the teachers mainly by analysis of the matters taught and didactic books accepted, the presence of elements of the Modern Mathematic movement. Furthermore, the search revealed the difficulties experienced by teachers which taught Mathematic the conquests and perspectives of a community which constitute itself in complete colonization process inside of Mato Grosso.